Novel Approach of Existence of Solutions to the Exponential Equation (3m2 + 3) x + (7m2 +1) y = z2 (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this manuscript the exponential equation (3m2 + 3) x + (7m2 +1) y = z2 where m Î Z in three variables for the occurrence of solutions belonging to the set  of all integers or the concerned equation has no solution for various alternatives of m is investigated.